Figurative Language Found in Mobile Legends Mage Hero Characters’ Voice Lines - Signora, Simanjorang La Veccia; Simatupang, Ervina CM (Linguistic, English Education and Art (LEEA) Journal, 2024)
This research aims to define the types of figurative language found and to explicate the functions of the voice lines in a game. The descriptive qualitative methodology is applied in this research, by scrutinizing the voice lines of the hero characters in the game, then inscribing and classifying the data obtained to then drawing conclusion about the data as the end of the steps. The data accumulated from 29 mage hero characters are 47 data. The figurative language found in the voice lines of mage hero characters of Mobile Legends are 11 data (23.40%) on personification, 9 data (19.14%) on metaphor, 5 data (10.63%) on simile, 15 data (31.91%) on hyperbole, and 7 data (14,92%) on paradox. The functions of language from the data analysed are 35 expressive function (75%), 9 informative function (19%), 3 aesthetic function (6%), while there is no data found on directive function and phatic function (0%). Hyperbole is the most used type of figurative language and simile is the least used type of figurative language; while the most used functions of language are expressive function and the least used is aesthetic function. Keywords: Figurative language; Functions of language; Game; Semantics